People's experiences of distress and psychosocial care following a terrorist attack: interviews with survivors of the Manchester Arena bombing in 2017. Issue 2 (3rd March 2022) - Stancombe, John; Williams, Richard; Drury, John; Collins, Hannah; Lagan, Lizzie; Barrett, Alan; French, Paul; Chitsabesan, Prathiba
Abstract : Background: Distress after major incidents is widespread among survivors. The great majority do not meet the criteria for mental health disorders and rely on psychosocial care provided by their informal networks and official response services. There is a need to better understand their experiences of distress and psychosocial care needs. Aims: The aims of our study were to enhance understanding of the experience of distress among people present at the Manchester Arena bombing in 2017, identify their experiences of psychosocial care after the incident and learn how to better deliver and target effective psychosocial care following major incidents. Method: We conducted a thematic analysis of semi-structured interviews with 18 physically non-injured survivors of the Manchester Arena attack, who registered with the NHS Manchester Resilience Hub. Results: Distress was ubiquitous, with long-lasting health and social consequences. Initial reluctance to seek help from services was also common. Early and open access to authoritative sources of information and emotional support, and organised events for survivors, were viewed as helpful interventions. Inappropriate forms of psychosocial and mental healthcare were common and potent stressors that affected coping and recovery. Conclusions: This paper extends our understanding of how people react to major events. Provision for the large group of people who are distressed and require psychosocial care may be inadequate after many incidents. There is a substantial agenda for developing awareness of people's needs for psychosocial interventions, and training practitioners to deliver them. The findings have substantial implications for policy and service design.